Behaviour‐driven micro‐scale niche differentiation in carabid beetles. Issue 1 (14th February 2015) - Kamenova, S.; Tougeron, K.; Cateine, M.; Marie, A.; Plantegenest, M.
Abstract Carabid beetles form rich and abundant communities in arable landscapes. Their generalist feeding behaviour and similar environmental requirements raise questions about the mechanisms allowing the coexistence of such species‐rich assemblages. We hypothesized that subtle niche partitioning comes into play on spatial, temporal, or trophic basis. To test this, we performed experiments and made observations on the behaviour of two sympatric carabid species of similar size and life cycle, Bembidion quadrimaculatum L. and Phyla obtusa Audinet‐Serville (both Coleoptera: Carabidae: Bembidiini). We compared plant climbing behaviour, daily activity patterns, and trophic preferences between the two carabid species under laboratory conditions. Whereas no clear difference in trophic preference was observed, our results suggest temporal niche differentiation at the nychthemeron scale (a period of 24 consecutive hours), with one of the species being more diurnal and the other more nocturnal, and spatial differentiation in their habitat use at the plant stratum scale. Intra‐specific variation suggests that micro‐scale spatio‐temporal niche differentiation could be mediated by behavioural plasticity in these two carabid species. We speculate that such behavioural plasticity may provide carabid beetles with a high adaptive potential in intensively managed agricultural areas.